2018
DOI: 10.1111/pin.12722
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous case of follicular lymphoma and Langerhans cell sarcoma in the same lymph node

Abstract: Langerhans cell sarcoma (LCS) is a very rare histiocytic and dendritic cell neoplasm originating from Langerhans cells. There are case reports of histiocytic and dendritic cell neoplasms synchronously or sequentially observed in patients with malignant lymphoma. We present a case in which LCS and follicular lymphoma (FL) grade 3a were observed within the same lymph node. A 66‐year‐old male visited our hospital with a general malaise. Pleural effusion and systemic lymph adenopathy were detected. Biopsy of an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In 2018, a case of FL and HCL development in the same lymph node was reported by Shimono J. et al. 1 Both tumor cells showed positivity of BCL6, IgH clonality and some identical amino acid sequences in direct sequence analysis of DNA. That case is important in demonstrating both association and developmental origin of those two distinct entities.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In 2018, a case of FL and HCL development in the same lymph node was reported by Shimono J. et al. 1 Both tumor cells showed positivity of BCL6, IgH clonality and some identical amino acid sequences in direct sequence analysis of DNA. That case is important in demonstrating both association and developmental origin of those two distinct entities.…”
Section: Discussionmentioning
confidence: 74%
“…Follicular lymphoma (FL) is one of the most common types of Non-Hodgkin Lymphoma (NHL) which originates from B-cells. 1 Generally it has an indolent clinical course, although histological transformation to aggressive lymphoma may occur in 25-35 % of cases, and therafter the prognosis has been reported to be poor. Transformation to histiocytic sarcoma may also be seen but very rarely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of this particular etiology is unclear and is still a matter of debate. Studies conducted within the last decade have also revealed that the development of LCS may not only be restricted to the histiocyte lineage but may also arise from hematopoietic tumors such as hairy cell leukemia, chronic lymphocytic leukemia/small lymphocytic lymphoma, and marginal-zone B-cell lymphoma [35][36][37][38][39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%